Application of nanomaterials in diagnosis and treatment of glioblastoma - Yu, Shuangqi; Chen, Lijie; Xu, Hongyu; Long, Shengrong; Jiang, Jiazhi; Wei, Wei; Niu, Xing; Li, Xiang (Frontiers in Chemistry, 2022)
Diagnosing and treating glioblastoma patients is currently hindered by several obstacles, such as tumor heterogeneity, the blood-brain barrier, tumor complexity, drug efflux pumps, and tumor immune escape mechanisms. Combining multiple methods can increase benefits against these challenges. For example, nanomaterials can improve the curative effect of glioblastoma treatments, and the synergistic combination of different drugs can markedly reduce their side effects. In this review, we discuss the progression and main issues regarding glioblastoma diagnosis and treatment, the classification of nanomaterials, and the delivery mechanisms of nanomedicines. We also examine tumor targeting and promising nano-diagnosis or treatment principles based on nanomedicine. We also summarize the progress made on the advanced application of combined nanomaterial-based diagnosis and treatment tools and discuss their clinical prospects. This review aims to provide a better understanding of nano-drug combinations, nano-diagnosis, and treatment options for glioblastoma, as well as insights for developing new tools.